Microfinance Performance in Urban Kathmandu: A Case Study of Lumanti Support Group for Shelter - Shrestha, Niyam Raj (PYC Nepal Journal of Management, 2010)
This study investigates microfinance performance of cooperatives established in slum and squatter areas of the urban Kathmandu supported by Lumanti: Support Group for Shelter. It specifically looks into the performance evaluation of the three cooperatives, analysis of the savings and credit and mobilization of groups and their members among the slum and squatter communities in the urban area of the Nepalese capital. The study methodology has combined the percentage analysis, trend and growth analysis and simple average statistical tools. The study has found the mobilization of saving and credit by the cooperatives of the slums and squatters as efficient.